Rapid circulation of HIV-1 CRF85_BC in Southwest China: its geographic origins and molecular transmission networks analysis - Liu, Yang; Yang, Cuixian; Chang, Wei; Fu, Xiaoyang; Zhang, Mi; Gao, Li; Liu, Li; Dong, Xingqi; Feng, Yue; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundUntil December 2024, China had identified and named 66 new HIV-1 recombinant genotypes. Among them, CRF85-BC is showing a rapidly growing trend in popularity in southwestern China, especially in Sichuan and Yunnan. This genotype was first discovered and reported in Sichuan and is believed to have originated in Yunnan. However, there are relatively few reports on the comprehensive systematic transmission data in Yunnan. This study will further elucidate the accurate evolutionary origin time and epidemic transmission dynamics of CRF85-BC.MethodsWe obtained 496 partial pol and 47 near full-length genomic sequences of HIV-1 CRF85_BC from 28,384 individuals with treatment failure in Yunnan, 2009-2023. Bayesian coalescent phylogeny analysis was performed to investigate the origin and timeline of CRF85_BC. A molecular transmission network was constructed using the genetic distance method to evaluate the transmission pattern. Spatial analysis was used to reveal the geographic patterns of phylogenetic clustering rates.ResultsThe number of CRF85_BC sample cases increased significantly between 2009 and 2023, and showed resistance to reverse transcriptase inhibitors (M184V/I and K103N/S). Bayesian phylogeny of nearly full-length sequences indicated that the emergence time in Yunnan was between January 1989 (95% confidence interval [CI]: 1984.9-1992.8) and February 1992 (95% CI: 1986.1-1996.6). Molecular networks resolved 87 transmission clusters, and the differences in transmission patterns were mainly manifested in the high aggregation rate (63.29%; 95% CI: 55.69%-70.89%) and cluster size (average size: 8.3) in Sichuan, which were higher than those in Yunnan (40.33%; 95% CI: 36.19%-44.47%; average size: 2.5). And all of them were heterosexual people, with a predominance of 77.81% (256/329). Spatiotemporal analysis revealed that Yunnan significantly transmitted to Sichuan, with Zhaotong and Yibin serving as key transmission hubs in both provinces.ConclusionsThe CRF85_BC genotype from Yunnan has a growing transmission network, with the potential for further expansion.